Keragaan Kacang Hijau (Vigna radiata L.) M2 Hasil Radiasi Sinar Gamma - Hs, Mansyur Andrawinsyah; Rasyad, Aslim; Isnaini, Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The purpose of this study was to determine genotypic performance of M2 generation of green beans resulting from gamma ray radiation compared to parents.Mung bean seeds from Kampar as M0 population and M2 generation from gamma ray radiation,were planted in the experimental station of the Faculty of Agriculture, University of Riau by using completely randomized design. The study was conducted by collecting quantitative traits of M0 and M2 generation from individual plant. Quantitative traits observed were plant height, number ofinternodes, number of primary branches, flowering date, harvesting date, number of pods per plant, number of seeds per pod, seed weight per plant, and 100 seedsweight. The result indicated that variation of harvesting date, number of filled pods per plant, number of seeds per plant, and seed weight per plant were greater in M2 population than in parentpopulation. Radiation of gamma ray shortened harvesting date, lengthened plant high and  increased number of seed per pod compered to M0, while other parameters were relatively the same between M2 and M0 population. Keywords: gamma ray radiation, phenotypic performance, mung bean, mutation.